Determinants of Corporate Credit Growth in Ukraine: The Application of Bank Lending Survey Data - Anatolii Hlazunov (Visnyk of the National Bank of Ukraine)
This study investigates the determinants of corporate lending in Ukraine, with a focus on distinguishing between supply and demand factors. It uses a two-step process to build a credit standards index (CSI) based on disaggregated data from a Ukrainian bank lending survey (BLS). This paper describes the factors that are significant for corporate lending development in Ukraine. It contributes to the existing literature by developing a measure of corporate loan supply and analyzing its ability to explain corporate credit growth in Ukraine by using bank-level BLS data. First, a panel ordered logit model is used to transform categorical data into a continuous index that measures the likelihood of credit standard tightening. Second, the study examines how this index affects new corporate lending in both national and foreign currencies. It is found that the credit standard index is influenced by exchange rate movements (with depreciations leading to tighter standards), bank liquidity, and bank competition. It is also demonstrated that the CSI has a negative impact on corporate loans in national currency, with a more pronounced effect on smaller banks.